Index cholecystectomy rates in mild gallstone pancreatitis: a single‐centre experience. Issue 10 (27th April 2020) - Butler, Reuban J.; Grieve, David A.
Abstract: Background: Gallstone pancreatitis (GSP) has evidence‐based guidelines regarding management. Both the International Association of Pancreatology/American Pancreatology Association and American College of Gastroenterology recommend index admission cholecystectomy (IAC) in patients presenting with mild GSP. The aim of this study was to examine guideline adherence and GSP recurrence rate when IAC was not performed. A comparison between admitting specialty was also performed to examine the difference in compliance rates. Methods: A retrospective chart review was conducted on all patients who presented to the Sunshine Coast Hospital and Health Service with GSP from December 2013 to December 2016. Patient demographics, timing of surgery, admitting specialty, laboratory and imaging results were recorded. Results: A total of 95 patients were identified with a first presentation of mild GSP during the study period. Of whom, 66 (69.5%) underwent IAC and 29 (30.5%) were discharged prior to cholecystectomy with 10 of those patients receiving index admission endoscopic sphincterotomy. Five patients (17%) who did not receive IAC were readmitted with gallstone‐related complications with the mean time to re‐presentation of 12.8 days (range 7–21 days). Patients were more likely to receive IAC when admitted under surgery compared with gastroenterology (76% versus 20%, P < 0.001). Conclusion: Two out of three patients presenting with mild GSP underwent IAC in accordance with evidence‐based management guidelines. Patients should be admitted under a surgical service to prevent delay in definitive management. Abstract : Gallstone pancreatitis has evidence‐based guidelines which recommend index admission cholecystectomy in patients with mild disease. A retrospective chart audit within the Sunshine Coast Health District found a 69.5% compliance rate to the guidelines. There was a 17% readmission rate in patients not receiving index cholecystectomy reinforcing the importance of guideline adherence.